2011
DOI: 10.1128/jcm.05031-11
|View full text |Cite
|
Sign up to set email alerts
|

Galactomannan Antigenemia after Infusion of Gluconate-Containing Plasma-Lyte

Abstract: We demonstrated that sodium gluconate was the factor causing false-positive galactomannan (GM) antigenemia of Plasma-Lyte hydration solution. Infusion of sodium gluconate-containing solution but not gluconate-free Plasma-Lyte resulted in positive serum GM antigenemia. Serum GM concentrations also correlated with the volume and in vitro concentrations of GM within gluconate-containing solutions of infused Plasma-Lyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…After discontinuation, GM tests became negative. The authors confirmed the false positivity of serum GM by testing several patients treated with Plasmalyte but without any sign of fungal infection (10 (12).…”
supporting
confidence: 53%
“…After discontinuation, GM tests became negative. The authors confirmed the false positivity of serum GM by testing several patients treated with Plasmalyte but without any sign of fungal infection (10 (12).…”
supporting
confidence: 53%
“…Previous studies have reported that patients and healthy volunteers receiving PL 148 have demonstrated a false-positive circulating galactomannan test lasting for up to 24 h[4-7]. Galactomannan antigen is a biomarker for pulmonary aspergillosis in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…D-F, Gomori methenamine silver staining (D; original magnification, ×400) shows acute angle-branching hyphae negative for anti-Aspergillus immunohistochemical staining (E; original magnification, ×400) but positive for anti-Rhizopus immunohistochemical staining (F; original magnification, ×400). products, or Plasma-Lyte [15][16][17]. In fact, all but 1 patient with PM whose GM assays were positive had received blood products or piperacillin-tazobactam, although the recent piperacillintazobactam preparations do not seem to cause false-positive GM results [18].…”
Section: Discussionmentioning
confidence: 99%